New mutants of Neurospora crassa highly resistant to the microtubule inhibitor benomyl - M. Tognolli; A. Utz-Pugin; G. Turian; C. Rossier (Fungal Genetics Reports, 1997)
Mutants of N. crassa highly resistant to benomyl with respect to hyphal growth were obtained by mutagenizing wild type strain St. Lawrence 74A or mutant Bml 511(r) which is moderately resistant to the fungicide. One of these, strain E1-91 that has a mutation mapping at the Bml (beta-tubulin) locus, showed temporary sensitivity to the benzimidazole.